Academic Programs of Economics: Comparative Analysis of Europe and Colombia - Prieto-Bustos, William (Universidad Pedagógica y Tecnológica de Colombia, 2022)
A sample of 22 European universities is compared with a sample of 7 Colombian universities located in Bogotá with undergraduate programs in Economics, using a benchmarking methodology defined by UNESCO for the identification of best curricular practices. To facilitate the identification of good practices in terms of research results, the sample of the European and Colombian universities was classified according to the research results ranking developed by Tilburg University (TUER). The results indicate the prevalence of eight trends in disciplinary development, in which the teaching of applied mathematics, languages, and elective courses in the social sciences stand out, the importance of the articulation of the foundation components, elective courses and research courses on problems defined based on the consolidation of an academic community in the economic sciences, particularly in Colombia.  This leads to two particular recommendations for the design of economics curricula in Colombia. On the one hand, the design of a pedagogy program in economics teaching with an ethical component and an evaluation orientation towards teaching practices is relevant for the management of knowledge about the scope of the foundation component on learning objectives. On the other hand, research and consulting require a more relevant orientation and articulation in the curricular programs based on an academic community with specific functions in the determination of economic problems of interest for economic development in Colombia.